Primary Malignant Melanoma of Esophagus: A Case Report - Kirti Rathod; Faruq Mulla; Munira Jhabuawala; Menka Shah (Medsci Publications, 2012)
Primary malignant melanoma of the esophagus is an extremely rare neoplasm representing 0.1% of all primary esophageal cancer with a mean survival of 2.2% at 5 years and a median survival of about 10 months. We present a case of a 54 year old man presented with a 2 month history of progressive dysphagia initially for solids and gradually progressed to semisolids along with history of change in voice. The patient had minimal weight loss and no family history of cancer. A pigmented polypoidal mass in the lower third of esophagus was diagnosed on upper GI scopy and confirmed as a malignant melanoma on biopsy.